Disease Problems of Rhino Captivation - Suzanna, Erna; Wresdiyati, Tutik (Media Konservasi, 2011)
Perhaps, the Javan Rhino (Rhmocerossondaicus) is the most endangered species among large animals in the world. Only two population of ~t are known in the world: one in Indonesia and another in l'ietnam. None exists in the zoos. The Javan Rh~no'sc aptivityis an alternative conse~vatione ffort to ensure their existence In the world. But it is imperative to give a correct immobilization, stable preparation such as in the natural forest. and also disease monitoring. Medication and preventive medicine for the Javan Rhino are vely important. Some diseases which have been encountered in the zoos are a.0.: helminthiasis. endocarditls, coliform d~arrheah. epat~tsb iliari.abscesses and slun lacerations can result in septicaemia. The sources of diseases In captivity can be some kinds of foods and water, animal keepers, equipment, contaminated place, rats and mice, birds and insects.